The Global Secondary Metabolite Regulator AcLaeA Modulates Aspergillus carbonarius Virulence, Ochratoxin Biosynthesis, and the Mode of Action of Biopesticides and Essential Oils - Maria K. Iliadi; Maria Varveri; Anastasia E. Kapetanakou; Panagiotis N. Skandamis; Dimitrios I. Tsitsigiannis (Toxins, 2024)
Aspergillus carbonarius is considered one of the main fungi responsible for black and sour rot in grapes, as well as the production of the carcinogenic mycotoxin ochratoxin A. The global regulatory methyltransferase protein LaeA controls the production of various secondary metabolites in Aspergillus species, as well as influences sexual and asexual reproduction and morphology. The goal of this study was to investigate the role of the regulatory gene AclaeA in physiology, virulence, and ochratoxin A (OTA) production by deleting this gene from the genome of a wild-type A. carbonarius strain. The evaluation data on the morphological characteristics, virulence experiments in three different grape varieties, and OTA analysis of ΔAclaeA mutants showed that the growth and the OTA production by ΔAclaeA strains were significantly reduced. The mutant strains were also less virulent, producing 40–50% less conidia in three different cultivars of grape berries. Additionally, the gene AclaeA was considerably repressed after the application of three commercial biopesticides (Trianum-P®, Vacciplant®, and Serenade® Max) and the essential oils (EOs) cinnamon, geranium, and thyme, which were also shown to inhibit OTA biosynthesis in A. carbonarius. The study of the regulatory gene AclaeA can contribute to a broader understanding of the role of secondary metabolites during A. carbonarius—grape interactions, as well as the discovery of the mode of action of biological plant protection products and EOs against this mycotoxigenic fungus.